COMPREHENSIVE APPLICATION OF THE PHYSICAL REMEDIAL TREATMENT AND PHYTOTHERAPY METHODS AMONG CHILDREN WITH CHRONIC RHINOSINUSITIS - E.I. Kondrat'eva; N.P. Stepanenko; S.E. Mishkova; S.S. Shakhova (Union of pediatricians of Russia, 2009)
Remedial treatment of children with chronic inflammatory diseases of nose and paranasal sinuses is urgent as this pathology is very widely spread in the childhood. In the present research, the authors studied an opportunity to perform a comprehensive treatment of children with chronic rhinosinusitis. The application of a phytomedication, physical treatment methods and their combinations showed the anti-inflammatory effect of the complexes, improvement of the morphofunctional status of the nose mucosa epithelial cells. Introduction of a phytomedication into the medical complex contributed to the reduction of rhinosinusitis exacerbations and cases of the acute respiratory infections among the examined patients.Key words: chronic rhinosinusitis, phytotherapy, physical treatment, children.